Edukasi Kesehatan Gigi di Taman Pendidikan Al-Quran (TPA) Kawashima, Jepang sebagai Upaya Peningkatan Ukhuwah Muslim Indonesia - Dian Yosi Arinawati; Nyka Dwi Febria; Afryla Femilian; Nadiya Putri Maharani; Sholahuddin (Dental Agromedis, 2023)
Kawashima is a city in Tokushima Prefecture, Japan. The worship activities carried out at the Kawashima prayer room include congregational prayers, namely Friday prayers, Eid al-Fitr and Eid al-Adha prayers and Al-Quran Education Park (TPA) activities for children. The number of children who took part in this activity was around 20 people, who were the sons and daughters of an Indonesian couple and an Indonesian-Japanese couple living in Kawashima. The problems faced by service target partners are language and infrastructure constraints. The majority of the Japanese population does not speak English. Likewise, Indonesian citizens in Japan are not fluent in English. Even though Indonesian citizens living in Japan are able to speak Japanese, this language is not the mother tongue of Indonesian citizens, so that it is possible to be constrained by a language barrier in communicating. This is a consideration for Indonesian citizens in communicating and accessing facilities that involve interaction with Japanese citizens, including in this case education regarding children's dental health. This is the background for the UMY court team to provide dental health education to children through TPA activities at the Kawashima prayer room. The educational method used is counseling using video media with the Indonesian language of instruction. The results of counseling show that there is an increase in knowledge of dental and oral health of parents before and after counseling.Keywords: Education, Japan, Dental and oral health, Indonesian Muslims, Qur'an Education Park, TPA